OTORITAS ORANG TUA DALAM MEMAKSA KAWIN ANAK USIA DIBAWAH 21 TAHUN MENURUT KHI - Hafidz Miftahuddin, Abdul (USRATUNA: Jurnal Hukum Keluarga Islam, 2024)
Marriage is a sacred institution in Islam, but the phenomenon of forced marriage, especially against minors, still occurs in Indonesian society. This article discusses the authority of parents in forcing child marriage based on the perspective of Islamic law and positive law in Indonesia. Based on Law Number 16 of 2019, the minimum age for marriage is 19 years, but violations in the form of early marriage for reasons of custom, economy, or family honor still often occur. In Islam, marriage must be based on the consent of both parties, as stated in the Compilation of Islamic Law (KHI) Articles 16 and 17. Forcing marriage without the consent of children is contrary to the principles of individual freedom and human rights. This article also examines the negative impacts of forced marriage on children's physical, psychological, and social well-being, such as the risk of divorce, loss of education rights, and reproductive health disorders. As a solution, it is necessary to increase legal awareness, formal education, and gender equality to prevent the practice of forced marriage. This study emphasizes the importance of involving children in decision-making related to marriage in order to realize a sakinah, mawaddah, and rahmah family life according to Islamic teachings and state law.